Elective gynaecological operations during sars-cov-2-pandemic. Durchführung von elektiven und benignen gynäkologischen operationen während der sars-cov-2-pandemie - Burghaus, Stefanie; Beckmann, Matthias; Hein, Alexander (Journal für Reproduktionsmedizin und Endokrinologie, 2021)
The SARS-CoV-2-pandemic led to a request in March 2020 for hospitals to postpone all medically not urgent operations, thus freeing up treatment and intensive care capacities. In gynaecology, this has particularly affected patients undergoing reproductive medical treatment, as well as patients with benign gynaecological diseases such as endome-triosis and uterine fibroids. The present study is intended to show how surgical interventions can be carried out during the SARS-CoV-2 pandemic, taking into account staff and patient safety, and what measures must be undertaken to do so. J Reproduktionsmed Endokrinol 2021; 18 (1): 8–12.
CRIS-Team Scopus Importer:2021-05-28
Keywords: COVID-19; Elective surgery; Gynaecology; SARS-CoV-2